Effect of Calcination Temperature and Strontium Addition on the Properties of Sol-Gelled Bioactive Glass Powder - Pei-Jung Chang; Jia-Yu Chen; Chi-Han Cheng; Kazuhiro Aoki; Cherng-Yuh Su; Chung-Kwei Lin (Gels)
Strontium-added bioactive glass (SBG) has been widely used in bone tissue engineering. SBG can be prepared by conventional high-temperature melt-quenching or calcining sol-gelled powder at 700 °C or above. In the present study, the effects of calcination temperature (400–650 °C) and the amount of strontium addition (0–7 mol.%) were investigated simultaneously. The sol-gel process and post-calcination were used to prepare the Sr-added 58S bioactive glass (SBG) powders. The bioactivity of the SBG powder was assessed by immersing it in simulated body fluid, while biocompatibility and cytotoxicity were evaluated using L929 and MG63 cells, and a zebrafish animal model. The calcination temperatures were determined by thermogravimetric analysis based on the weight loss at various stages. X-ray diffraction was used to reveal the crystalline structure of calcined or SBF-immersed SBG powders. Meanwhile, the texture characteristics of SBG powders were examined by the BET method. Fourier-transformed infrared spectroscopy and scanning electron microscopy were used to investigate the absorption bands and powder morphology of SBG powders before and after SBF immersion. The experimental results showed that all SBG powders were mesoporous with a high specific surface area larger than 200 m2/g. SBG powder calcined at 650 °C with 5% Sr addition possessed a major Ca14.92(PO4)2.35(SiO4)5.65 phase, the smallest pore size of 5.86 nm, and the largest specific surface area of 233 m2/g. It was noncytotoxic and exhibited good bioactivity and biocompatibility.